2017
DOI: 10.1186/s12711-016-0278-x
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of economic values for production traits in aquaculture species

Abstract: BackgroundIn breeding programs for aquaculture species, breeding goal traits are often weighted based on the desired gains but economic gain would be higher if economic values were used instead. The objectives of this study were: (1) to develop a bio-economic model to derive economic values for aquaculture species, (2) to apply the model to determine the economic importance and economic values of traits in a case-study on gilthead seabream, and (3) to validate the model by comparison with a profit equation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 54 publications
1
27
0
5
Order By: Relevance
“…Por lo que el segundo objetivo de esta investigación se enfocó en realizar un análisis de rentabilidad del cultivo de tilapia nilótica utilizando diferentes estrategias de alimentación y diferentes escenarios de evaluación de la relación beneficio/ costo y el NPV. Integrando al modelo los criterios analíticos propuestos por Janssen et al (2017) en las variables biológicas y los criterios desarrollados por Perea-Román et al (2018), así como también los de Phiri & Yuan (2018) en los índices de rentabilidad económica y en los coeficientes de sensibilidad determinados en este modelado con tilapia.…”
Section: P a L A B R A S C L A V Eunclassified
See 2 more Smart Citations
“…Por lo que el segundo objetivo de esta investigación se enfocó en realizar un análisis de rentabilidad del cultivo de tilapia nilótica utilizando diferentes estrategias de alimentación y diferentes escenarios de evaluación de la relación beneficio/ costo y el NPV. Integrando al modelo los criterios analíticos propuestos por Janssen et al (2017) en las variables biológicas y los criterios desarrollados por Perea-Román et al (2018), así como también los de Phiri & Yuan (2018) en los índices de rentabilidad económica y en los coeficientes de sensibilidad determinados en este modelado con tilapia.…”
Section: P a L A B R A S C L A V Eunclassified
“…Tilapia is a popular fish in the world freshwater aquaculture with 126 reported countries or regions, in which a production of 5.7 MT was recorded in 2015, according to data from FAO (2016). A relevant goal to keep this sector constantly growing involves developing new researches aiming to determine the benefits of using different feeding strategies, and how these strategies influence economic and productive parameters (Gutiérrez et al, 2015;Janssen et al, 2017). mismas dietas con un modelo de alimentación con restricción del 30 % (alimentación diaria al 70 %).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main obstacles in incorporating uniformity in aquaculture breeding programs is often high and positive genetic correlation between level and variance of harvest weight, meaning that selection for uniformity will cause decrease in selection response in body weight, which is highly undesirable, especially giving the 161 low economic value of uniformity (Janssen et al, 2017). It would be interesting to see how indirect genetic effects for b correlate with genetic effects for body weight, and whether selection on IGEs only, could be used to improve uniformity, without consequences for growth.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In aquaculture, uniformity of body weight has recently been identified as one of the most important traits to be improved by selective breeding (Sae-Lim et al, 2012;Janssen et al, 2017;Omasaki et al, 2017). Studies in Atlantic salmon, rainbow trout, and Nile tilapia found a large genetic component in variability of body weight (Janhunen et al, 2012;Sonesson et al, 2013;Sae-Lim, et al, 2015a;Sae-Lim, et al, 2015b;.…”
Section: Social Interactions and Inherited Variabilitymentioning
confidence: 99%